The Mediating Role of Environmental Performance on Green Intellectual Capital and EMA’s Impact on Corporate Sustainability - Archita Nuari Sasika; Irwansyah Irwansyah; Muhammad Ikbal (PT. Publikasiku Academic Solution, 2025)
The purpose of this research is to analyze (1) The effect of green intellectual capital and environmental management accounting on environmental performance and corporate sustainability, (2) Environmental performance mediates the effect of green intellectual capital and environmental management accounting to corporate sustainability. The current research utilizes the quantitative research methods with secondary data and also content analysis from the sustainability report and annual report of the company. The target population consist of companies with high esg risk that publish Annual Reports and Sustainability Reports which listed on the Indonesia Stock Exchange in 2019-2024. Data of this research selected trough purposive sampling with panel data regression and obtained 96 observations. The result obtained in this research found that in the high esg risk companies, green intellectual capital has a significant positive impact to environmental performance and corporate sustainability. Environmental performance significantly mediates the effect of green intellectual capital on corporate sustainability. Meanwhile the environmental management accounting couldn’t shows the significant impact on environmental performance and corporate sustainability. In summary, this research supports the resource based view theory and conclude that green intellectual capital can be a good resource to achieve an excellent environmental performance, and lead the companies to corporate sustainability than environmental management accounting that needs to be integrate with other materials source to shows the same impact.